Sufi orders and Islamic sectarianism in China: origin and early development - Min, Keqin; Mai, Jianjun (Science Publishing Group (SciencePG), 2025)
In the studies on Islam, Sufism is an unavoidable topic, so is with Chinese Islam. This paper focuses on Chinese Islamic Sufi orders and sectarianism. Since the length of the paper is quite long, it is divided into two parts, under slightly different titles. The first title is above stated, while the second will be “Sufi Orders and Sectarians: The Shattering Chinese Muslims Unity”. It is intended by this paper to provide the reader a fuller and clearer picture on Chinese Sufism and sectarianism, whose introduction into the country since beginning stirred up disputes and conflicts within Muslim community, later spilled out the community, and escalated to common rebellion against Qing government (1644-1911) from 1862 to 1878. In this first part, the author traces the fountain sources of those orders and sectarians, often to Arab nations and Central Asia, even Muslim India. In the discussion, the author redivides those orders and sectarians into three categories: one traditional school (Qedim sect), three movements (Xidaotang, Ikhwan, and Salafiyya), and four Sufi orders (Jehriyya, Khufiyya, Qadiriyya, Kubrawiyya). Based on the existing materials, mainly Ma Tong’s field research work, which provides the firsthand information on Chinese Sufi orders and sectarianism, the author delineates the formation of those Sufi orders and sectarians, so to lay a solid foundation for further discussion of their later development, analyzing the causes and reasons of later disputes and conflict. This paper does not claim to be creative and all-inclusive but try to provide the reader a fuller contour of Chinese Islam. It best can be complementary to the existing body of similar research.